Occult Cortical Dysplasia and Focal Status - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Four patients, ages 4, 6, 13, and 21 years, with life-threatening focal motor status epilepticus, normal pre-operative MRI, and focal cortical dysplasia defined only in the surgical specimens obtained by corticectomies, are reported from the Montreal Neurological Institute; Austin Hospital, Heidelberg, Australia; University of California, San Francisco; and Royal Children's Hospital, Melbourne, Australia.